SUPPORTING CRITICAL THINKING SKILLS IN BLENDED LEARNING ENVIRONMENT: A QUALITATIVE STUDY IN MATHEMATICS DEPARTMENT, MEDAN STATE UNIVERSITY - Muliawan Firdaus; Mukhtar Mukhtar; Zainal Azis (Universitas Negeri Medan, 2020)
Abstract: Supporting Critical Thinking Skills In Blended Learning Environment: A Qualitative Study In Mathematics Department, Medan State University. Supporting critical thinking skills is one of the most important goals of many educational institutions. With the rapid development of internet technology, education practitioners are trying to improve critical thinking through online learning systems. This study aims to explore the experience of lecturers and students of the Mathematics Education Study Program related to efforts in supporting critical thinking skills in the Medan State University Online Learning System. Data was collected through semi-structured interviews. The results of the interview were conceptualized in two main themes: learning design and management. This study clarifies factors that influence efforts in supporting critical thinking skills in blended learning settings.Keywords: Critical Thinking Skills, Blended Learning Environment, Mathematics Education.Abstrak: Mendukung Keterampilan Berpikir Kritis Dalam Lingkungan Belajar Campuran: Studi Kualitatif di Departemen Matematika, Universitas Negeri Medan. Meningkatkan keterampilan berpikir kritis adalah salah satu tujuan terpenting dari banyak lembaga pendidikan. Dengan semakin cepatnya perkembangan teknologi internet, praktisi pendidikan berupaya untuk meningkatkan pemikiran kritis melalui sistem pembelajaran daring. Penelitian ini bertujuan untuk mengeksplorasi pengalaman dosen dan mahasiswa Program Studi Pendidikan Matematika terkait upaya dalam mendukung keterampilan berpikir kritis dalam Sistem Pembelajaran Daring Universitas Negeri Medan. Data dikumpulkan melalui wawancara semi terstruktur. Hasil wawancara dikonseptualisasikan dalam dua tema utama: rancangan pembelajaran dan manajemen. Penelitian ini mengklarifikasi faktor-faktor yang mempengaruhi upaya dalam mendukung kemampuan berpikir kritis dalam pengaturan pembelajaran campuran.Kata Kunci: Keterampilan Berpikir Kritis, Lingkungan Pembelajaran Campuran, Pendidikan Matematika.